Fabrication of microfluidic droplet former. - Chye, Jessica Yan Mei. (2012)
The main focus of this project will be the fabrication and assembly of a working microfluidic device. Microchannel production is a three step process. First, UV lithography is used to fabricate the reusable master. Polydimethylsiloxane, commonly known as PDMS, is then used to cast the master thus creating the microchannels via soft lithography. Finally, the PDMS is then bonded onto a glass slide and ready for use. There are many promising applications for microfluidic devices, with one of the first pioneering applications integrated in ink-jet printers by Hewlett-Packard. Today, Lab-on-a-chip technologies can be seen in many day to day applications like blood glucose monitors, to forensic investigation kits where the quantity of the biological media in question is very limited. Due to its vast potential, this field is constantly researched to find cheaper alternatives with high yield. Typical flow focusing microfuidic channels are the main focus of this project. Experiments have been done to fine tune the fabrication steps as mentioned. Both successes and failures were documented.